KINETIC STUDY OF PHOTODEGRADATION OF Azo DYES WITH TiO2 UNDER VISIBLE LIGHT - Habeeb, Hassan A; Kadhum, Abbas A A (Al-Nahrain Journal of Science, 2018)
In this work, two mono azo dyes : 4-(2- benzoic acid azo )-m-amino phenol (BAMAP), and4-(2-benzoic acid azo)-P-amino phenol (BAPAP)have been synthesized and identified by FT-IRspectroscopy. UV-Visible absorption spectra were recorded and some physical and chemicalproperties have been listed.The photodegradation of dyes was investigated by using the light of tungsten lamp in presenceand absence of titanium dioxide (anatase). It has been found that the increasing of TiO2 masscaused an increasing in photodegradation of two dyes until the optimum mass (2gm/l) was reached.Also, the results indicate, that the basic media give more photodegradation rate than acidic medium,moreover ,the effect of temperatures in the range (298 323K) on degraded dye was studied ,and theactivation energy of photodegradation processes was calculated from Arrhenius plot which equal35.82KJ.mol-1for BAMAP and 32.11KJ.mol-1for BAPAP.The results showed the photoreaction is1st order ,with decomposition constant equal 2.362x10-4min-1for BAMAP and 2.826x10-4 min-1forBAPAP at 298k and neutral medium.Generally, it has been found that the rate of photodegradation of BAPAP is more than BAMAP,and the decolonization rate of the two dyes was higher in presence of TiO2 suspension.